Cam Jansen, the mystery of the dinosaur bones - Adler, David A. (New York : Puffin Books, 2004)
When she notices some bones missing from a dinosaur skeleton exhibited in the museum, a young girl with a photographic memory tries to discover who has been taking them and why.
K
b
b